ANALYSIS OF TAYLOR DE' VIRDIS PRODUCT PURCHASE DECISIONS THROUGH LIVE STREAMING SESSIONS ON TIKTOK SOCIAL MEDIA - Tamara Marsya Safitri; Virdies Nur Cahya (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the decision-making process for purchasing Taylor De' Virdis products through live streaming sessions on the social media platform TikTok. In examining this topic, the researcher used a descriptive qualitative method with a netnographic approach. Data collection was carried out through digital observation by joining the internet community as a live host. Data was obtained from live streaming archives from June 2025 and analyzed step-by-step using the netnography method: entry, data collection, analysis, and interpretation. This study was analyzed based on Kotler & Armstrong's consumer decision-making theory. The results of this study indicate that the purchasing decision process during Taylor De' Virdis' live streaming on TikTok involves five distinct stages, namely: (1) the emergence of a need due to live streaming content recommendations, (2) interactive information search through the comment section, (3) evaluation of alternatives influenced by real-time product demonstrations, (4) purchase decisions based on careful consideration and rational judgment, and (5) post-purchase satisfaction dependent on the accuracy of information provided by the host.